Euphoric, Harmless, and Affordable. - Moloney, Karen (Futurist)
The article focuses on technological developments affecting euphoric, harmless, and affordable (EHA) sex. Topics discussed include enhanced delivery of medicines by technologies such as human-computing interactions, remote technologies, and robotics, improved functionality of sex toys, and physicist Stephen Hawking's work to combine brain power and technology for improved sex life.